تعلم اللغة العربية ببرنامج زوم في عصر كورونا في جامعة الإسلامية تنجكوا ديروندنج مولابوه - armawi, sullati (Faculty of Education and Teachers Training of UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
مستخلص البحث : تهدف هذه الدراسة لوصف عملية تعلم اللغة العربية ببرنامج زوم في الجامعة الإسلامية تنجكوا ديرندنج مولابوه بأتشية غربية و تحليل مزايا و عيوبها. استخدمت الباحثة المدخل الكيفي و المنهج الوصفي في وجود البيانات. ثم حللت الباحثة عن البيانات بنظرية التحليلية مايليس وهيبرمان منها تكثيف البيانات و عرضها و إستنتاجها. أما نتائج البحث فهي أن تعلم اللغة العربية ببرنامج زوم هو نقل العلوم من مراكز تجمعه إلى أماكن بعيدة، و يتم الاتصال بين المعلم و المتعلم تفاعليا، يستطيع المعلم أن يلقي المحاضرات و الدروس ولو كان مكان التعلم بعيد من مصدر مكان المعلم. أما مزايا هذا البرنامج منها يشعر المعلم سهولة في شرح المادة من خلال عرض شاشة المشاركة حتى يكون التفاعل بينهم بشكل مباشر، و يجيد زيادة حماسة التعلم في نفس المتعلمين و يزيد الخبرة للمتعلم في أنشطة التعلم جديدة. الكلمة المفتاحية : تعلم اللغة العربية، برنامج زوم Abstract: This study aims to describe the process of learning the Arabic language using zoom meeting application at the Islamic University of Teungku Dirundeng Meulaboh in West Aceh, and to analyze its advantages and disadvantages. The researcher used the qualitative approach and the descriptive approach in the presence of the data. Then the researcher analyzed the data with the analytical theory of Miles and Huberman, including data condensation, presentation and conclusion. As for the results of the research, learning Arabic language using Zoom meeting application is able to transfer knowledge from regular places to distant places, and communication is made between teacher and learners interactively, the teacher can deliver lectures and lessons even the place of learning is far away from the teacher’s place. As for the advantages of this program, the teacher feels easy to explain the material by displaying the participation screen so that the interaction between them is established, and it is good to increase the enthusiasm for learning in the same learners and increase the experience of the learner in new learning activities. Keyword : learning the Arabic language, Zoom Meeting Application Abstrak: Penelitian ini bertujuan untuk mendeskripsikan proses pembelajaran bahasa Arab menggunakan aplikasi zoom meeting di Universitas Islam Teungku Dirundeng Meulaboh Aceh Barat, serta menganalisis kelebihan dan kekurangannya. Peneliti menggunakan pendekatan kualitatif dan pendekatan deskriptif dengan adanya data. Kemudian peneliti menganalisis data dengan teori analisis Miles dan Huberman, meliputi kondensasi data, penyajian dan penarikan kesimpulan. Adapun dari hasil penelitian, pembelajaran bahasa Arab menggunakan aplikasi Zoom meeting mampu mentransfer ilmu pengetahuan dari tempat biasa ke tempat yang jauh, dan komunikasi terjalin antara guru dan peserta didik secara interaktif, guru dapat menyampaikan ceramah dan pembelajaran meskipun tempat belajarnya berada. jauh dari tempat guru. Adapun kelebihan dari program ini adalah guru merasa mudah dalam menjelaskan materi dengan menampilkan layar partisipasi sehingga terjalin interaksi diantara mereka, serta baik untuk meningkatkan semangat belajar pada peserta didik yang sama dan menambah pengalaman peserta didik. pembelajar dalam kegiatan pembelajaran baru. Kata Kunci : Pembelajaran Bahasa Arab, Aplikasi Zoom Meeting